Reproducing Charisma: A Study of Religious Pilgrimage to Hasan Genggong’s Cemetery in Pajarakan Probolinggo - Abdurrahman Abdurrahman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2017)
The annual death celebration (haul) to religious figure is a key instance of the commodifications of prosperity Islamic mode at institutional level, where strong modern business organizational skills are matched with charismatic leadership. This study implies that successful market mechanism makes haul a consumer commodity attractive to spirituality hungry middle class Muslim community in Probolinggo. It ethnographically observes the intertwining of market and Islam where Muslims community looked to the market as a critical source for experiencing and publicizing a sense of sacred identity. Commodification of religion is deeply embedded in the haul or regularly ziarah (pilgrimage) for every 11 Syawal to Muhammad Hasan, a passed away central figure of kiai in Pesantren Zainul Hasan Genggong Probolinggo, and it makes a strong presence in the spiritual marketplace through commodifications of Kiai Hasan’s amulet and memorabilia, including his photos, tasbih, jimat, akik, and others. This study also reflects on the possible effect of charisma in undermining the sense of authenticity and authority of charismatic Kiai Hasan among the Muslim community in Probolinggo, and the ways it effects on the construction of spiritual market surrounding his cemetery.